Supplemental video 1 and video 2 to preprint article: Surface acoustic wave integrated microfluidics for repetitive and reversible temporary immobilization of C. elegans - Sridhar, Nakul, author and filmmaker (Colorado State University. Libraries, 2022)
The ZIP file contains two supplemental videos to the preprint article: BIORXIV/2022/496864; Surface Acoustic Wave Integrated Microfluidics for Repetitive and Reversible Temporary Immobilization of C. elegans by Nakul Sridhar, Apresio Kefin Fajrial, Rachel L. Doser, Frederic L. Hoerndli, and Xiaoyun Ding.
No audio.
Keywords: Nematodes